Uji Praktikalitas Media Pembelajaran Berbasis Android Pada Mata Pelajaran Pendidikan Jasmani Olahraga dan Kesehatan Kelas XI di SMK N 2 Padang - Teza Julita; Yuliawati Yunus; Indra Wijaya (CV Putra Publisher, 2023)
This study aims to determine the Validity, Practicality and Effectiveness of the Design and Development of Android-Based Learning Media Applications in Class XI Physical Education Sport and Health Subjects at SMK N 2 Padang in Academic Year 2022/2023. This research uses research & development methods (research & development). Subjek research amounted to 45 people. The research model used is the development research model (ADDIE model), with the design of the development steps as follows. (1) Analyze, (2) Design, (3) Development, (4) Implementation dan (5) Evaluate. The results of the validity test by the experts as a whole the validator test assessment of the Android-based Learning Media Application in Physical Education, Sports and Health Subjects Class XI at SMK Negeri 2 Padang was 91.75%. So that the level of validity can be interpreted as very valid to use. The results of the practicality test assessment as a whole the practicality assessment of the Application of Android-Based Learning Media in Class XI Physical Education Sports and Health at SMK Negeri 2 Padang is 91.04%, so that the level of practicality can be interpreted as very practical to use. The results of the overall effectiveness test assessment of the effectiveness of the Android-based Learning Media Application in Class XI Physical Education Sports and Health at SMK Negeri 2 Padang amounted to 87.82%, so that the level of effectiveness can be interpreted to be used very effectively. Conclusion, based on the assessment along with expert input as well as the results of field trials of the Android-Based Learning Media Application as a learning medium that has been tested for feasibility, superiority, and can be used in the learning process in Class XI Physical Education Sports and Health Subjects at SMK Negeri 2 Padang.